1998
DOI: 10.1002/(sici)1521-4176(199807)49:5<330::aid-maco330>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Metal dusting of 9 - 20% Cr steels in increased pressure environments at 560°C

Abstract: The susceptibility of steels to catastrophic failure by metal dusting is known to depend upon the activity of the carburising environment, alloy chromium content, grain size, surface condition and temperature. This paper presents results of first tests investigating the influence of gas pressure on metal dusting of 9 – 20% Cr containing steels, by increasing the test gas pressure to approximately five bar over atmospheric pressure. Cross‐sectional micrographs show attack morphologies such as intergranular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The effect of pressure is not commonly investigated but more severe metal dusting attack has been reported with increasing test pressure [11,[17][18][19]. Contrary to Hochman who explained that low P O 2 and a c sites are favorable for metal dusting [40], Nishiyama et al [17] considered that an increase in P O 2 is harmful because it lowers the oxide scale integrity by creating defects.…”
Section: Carbon Activity Equal To 10 While Increasing H 2 O% and Totamentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pressure is not commonly investigated but more severe metal dusting attack has been reported with increasing test pressure [11,[17][18][19]. Contrary to Hochman who explained that low P O 2 and a c sites are favorable for metal dusting [40], Nishiyama et al [17] considered that an increase in P O 2 is harmful because it lowers the oxide scale integrity by creating defects.…”
Section: Carbon Activity Equal To 10 While Increasing H 2 O% and Totamentioning
confidence: 99%
“…A large number of studies have been devoted to define which alloys and compositions [1][2][3][4][5][6][7][8] are more resistant to metal dusting. The influence of alloy grain size [3,9], surface finish, cold working [3,[9][10][11][12] or the addition of a coating [13][14][15][16] on the resistance to such corrosion has been evaluated. Other studies were interested in the effect of parameters defining the metal dusting environment: temperature [12,17], total pressure [11,[17][18][19] or gas composition [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Metal dusting is a very complex type of corrosion which depends on the nature of the alloy [8,9], its microstructure [10,11] and composition [12,13]. Of course, it is also greatly influenced by the atmosphere composition [3,8,14], the temperature [15,16] and the overall pressure [17,18]. Due to the low oxygen partial pressure (below 10 −20 bar), only very stable oxides such as chromia, alumina, silica or some spinels can form.…”
Section: Introductionmentioning
confidence: 99%
“…al. [34,35]. Initial conclusions drawn from the experiments indicated that there was a tendency for increased attack with increasing pressure and that as the pressure increased the surface condition becomes more important.…”
Section: Introductionmentioning
confidence: 99%